Argiope hoiseni, a new species of the spider genus Argiope (Araneae, Araneidae) from Peninsular Malaysia based on morphology and molecular analyses - Tan, Ji (Zootaxa, 2018)
A new species of Argiope Audouin 1826, A. hoiseni new species is described from Perak and Selangor, Peninsular Malaysia based on morphology and DNA information of the mitochondrial (16S rRNA, COI and COII) and nuclear-encoded (H3A, 18S rRNA) molecular markers. Epigynal structure suggested Argiope hoiseni to be similar to A. jinghongensis Yin, Peng & Wang 1994, A. luzona (Walckenaer 1841), A. pulchella Thorell 1881 and A. taprobanica Thorell 1887. Molecular sequence data including the new species inferred that it is monophyletic with an intraspecific variation of 0.87–3.59 % based on the 16S+COI+COII+H3A dataset. Phylogenetic analyses also revealed insights into the evolutionary lineages of Argiope species in Southeast Asia as well as corroborated recent taxonomic changes and species synonymies associated with Argiope. Two new distribution records were also reported for A. chloreis Thorell,1877 and A. doleschalli Thorell, 1873 in Peninsular Malaysia.